ROLE OF ENZYMES IN THE GERMINATION PROCESS - VIDAURRETA ONDARZA, RAUL; OLIVE, JUAN (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1942)
Expts on several kinds of seed indicate that (a) the process of germination involves various factors, predominant among which is the action of enzymes; (b) the opt pH for action of ferments is different in different seeds, for amylases of beans, 54, fo
REV SOC MEX HIST NAT
Keywords: ROLE, ENZYMES, GERMINATION PROCESS; CIENCIAS DE LA VIDA